Design and Development of an Integrated Attendance and Task Management Application Based on Android - M. Putra Ramadhani; Syarifah Aini; Karnadi Karnadi (Yayasan Cita Cendekiawan Al Khwarizmi, 2026)
Employee attendance and task management are important elements in maintaining organizational productivity, accountability, and operational efficiency. Conventional attendance systems, such as manual recording and fingerprint devices, still face several limitations including fraud potential, inaccurate data recording, and lack of flexibility for field employees. This research aims to design and develop an integrated Android-based attendance and task management application by utilizing Global Positioning System (GPS), Location Based Service (LBS), visual attendance validation, and real-time task monitoring features. The system was developed using the Rapid Application Development (RAD) approach combined with Agile Development to accelerate system implementation through iterative processes and continuous user feedback. The application integrates attendance recording, GPS location validation, employee task assignment, progress monitoring, and deadline notifications into a single platform. System testing was conducted using the Black-box Testing method to evaluate application functionality and reliability. The results show that the developed system successfully performs core functions such as login, GPS-based attendance, task management, attendance reports, and task monitoring with a testing success rate of 94%. The system is also capable of reducing attendance manipulation through real-time location validation and activity monitoring mechanisms. This research contributes an integrated mobile solution that improves attendance accuracy, task transparency, work efficiency, and employee productivity in organizations with high workforce mobility.